Content of interleukins-4, 6 and nuclear transcription factor NF-κB in children with atopic bronchial asthma depending on Ile50Val polymorphism of IL4RA gene, severity of the disease course and level of its control - V. M. Dudnyk; L. V. Moroz; N. V. Zaichko; O. V. Kutsak (Zaporožskij Medicinskij Žurnal)
Many studies on polymorphic variants of cytokines genes indicate that their role in bronchial asthma development in children is still not fully understood.